2013
DOI: 10.3109/02656736.2013.783934
|View full text |Cite
|
Sign up to set email alerts
|

Clinical integration of software tool VEDO for adaptive and quantitative application of phased array hyperthermia in the head and neck

Abstract: This analysis shows that VEDO facilitates a quantitative treatment strategy allowing standardised application of HT by technicians of different HT centres, which will potentially lead to improved treatment quality and the possibility of tracking the effectiveness of different treatment strategies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
118
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 82 publications
(118 citation statements)
references
References 36 publications
0
118
0
Order By: Relevance
“…An advantage of hyperthermia is that the thermal dose delivered is regularly measured during the 1-h treatment using temperature probes or with non-invasive MR thermometry. This permits online re-planning yielding adapted settings correcting the thermal dose distribution during the session itself [65][66][67][68]. It also permits retrospective reconstruction of the given thermal dose distribution during each session, followed by re-planning the optimal thermal dose distribution for the remaining sessions based on the cumulative dose already given.…”
Section: Further Researchmentioning
confidence: 99%
“…An advantage of hyperthermia is that the thermal dose delivered is regularly measured during the 1-h treatment using temperature probes or with non-invasive MR thermometry. This permits online re-planning yielding adapted settings correcting the thermal dose distribution during the session itself [65][66][67][68]. It also permits retrospective reconstruction of the given thermal dose distribution during each session, followed by re-planning the optimal thermal dose distribution for the remaining sessions based on the cumulative dose already given.…”
Section: Further Researchmentioning
confidence: 99%
“…Some research groups explore the possibility to combine treatment planning with MRI feedback [81][82][83], but this requires MR-compatibility of the heating system. Therefore also on-line adaptive use of treatment planning is currently investigated [84][85][86]. The feasibility has been demonstrated by a study, which showed that there is a correlation between measured and predicted changes in SAR after phase steering [54].…”
Section: Discussionmentioning
confidence: 99%
“…At our institute, HTP is mandatory prior to HYPERcollar treatments to optimise amplitude and phase settings for each channel in the phase array, and the patient position in the applicator [11,12,16]. HTP also ensures that the specific absorption rate (SAR) in critical tissues such as spinal cord does not exceed safety limits of 60 W/kg [13]. Our in house tool VEDO allows technicians to adjust amplitude and phase settings during treatment according to measured temperatures and patient feedback [13].…”
Section: Hyperthermia Treatment Planningmentioning
confidence: 99%
“…HTP also ensures that the specific absorption rate (SAR) in critical tissues such as spinal cord does not exceed safety limits of 60 W/kg [13]. Our in house tool VEDO allows technicians to adjust amplitude and phase settings during treatment according to measured temperatures and patient feedback [13]. Superficial HTP setups were created manually by an experienced physicist (TD) in order to overlap the CTV with at least ten millimetres by the LCA or CSA aperture.…”
Section: Hyperthermia Treatment Planningmentioning
confidence: 99%
See 1 more Smart Citation